The Effect of Galoba (Hornstedtia sp.) Fruit Extract on Malondialdehyde (MDA) Serum Level of Hyperglycemic Mice (Mus musculus) Streptozotocin-Induced - Yuan Ivani Rumengan; Indrawanti Kusadhiani; Rachmawati Dwi Agustin (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Hyperglycemia or increased blood sugar levels is a sign of diabetes mellitus. In hyperglycemia, there will be an increase in Reactive Oxygen Species (ROS) in the body so that it will lead to a state of oxidative stress characterized by an increase in malondialdehyde (MDA) levels. Galoba fruit is an endemic fruit in Maluku Province that contains antioxidants. Antioxidants contained in galoba fruit can help endogenous antioxidants to overcome oxidative stress. Objective: This study aims to determine the effect of galoba fruit extract on serum MDA levels of hyperglycemia mice induced by streptozotocin. Methods: This study is an experimental study with post-test only control group design and random sampling. The sample consisted of 24 mice divided into 6 groups, namely normal control (KN), negative control (K-), positive control (K+), treatment 1 (P1), treatment 2 (P2), and treatment 3 (P3). The KN group was only given a standard diet, the K- group was only induced streptozotocin, the K+ group was induced streptozotocin and treated with metformin for 21 days, and the P1, P2, and P3 groups were induced streptozotocin and given galoba fruit extract concentrations of 100%, 75%, and 50% for 21 days. After treatment, the mice were dissected to collect blood serum from the heart of the mice to measure MDA levels. Serum MDA levels were measured by the TBARS method. Results: The average serum MDA levels of the KN, K-, K+, P1, P2, and P3 groups were 358.75 nmol/mg, 1278.75 nmol/mg, 522.08 nmol/mg, 526.16 nmol/mg, 442.66 nmol/mg, and 432.41 nmol/mg. MDA data obtained was then tested with one way ANOVA and obtained a value of p=0.00 (<0.05). Conclusion: Based on the Tukey test, both P1, P2, and P3 have the same effect on reducing serum MDA levels of mice after being induced by streptozotocin with P3 providing the greatest decrease.